Pendapatan dan Produksi Potensial Usahatani Konservasi Lahan Pantai di Kabupaten Bantul - Widodo, Aris Slamet (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Yogyakarta, 2015)
Coastal land management are expectedÂ not only serves as an erosion controlÂ (wind), but also serves to increaseÂ farmerâs incomes. This study aims toÂ analyze the income and the potentialÂ production of conservation farmingÂ system on coastal land in Bantul. TheÂ survey was conducted in the village ofÂ Srigading and Gadingsari Bantul. IncomeÂ and potential production of four mainÂ commodities, namely red onions, redÂ peppers, eggplant, and sweet potatoesÂ were analyzed using Technical EfficiencyÂ Effect Model. Results of the studyÂ showed that from 0.1 hectares of coastalÂ land, the farmers obtain the highestÂ revenue of red pepper, which amountedÂ to Rp 3.9 million in the dry season 1 andÂ Rp 2.5 in the dry season 2; followed byÂ red onions income, amounted to Rp 2.1 million in the rainy season and Rp1.6Â in the dry season; while eggplant provide the lowest income, whichÂ amounted to Rp 98 thousand in the rainy season. The estimation results ofÂ Cobb-Douglas Stochastic Frontier Model with MLE method showed anÂ increase in the potential of onion in the rainy season by 7.4%; eggplantÂ 11.4% and 10.2% sweet potato. In the dry season 1, there is an increase inÂ onion production by 10.6%; red chili 4% and 5.6% sweet potato. While inÂ the dry season 2, there is an increased production of red onion and eggplantÂ by 4.1% at 6.1%.